2018
DOI: 10.3892/or.2018.6699
|View full text |Cite
|
Sign up to set email alerts
|

Allergen‑removed Rhus�verniciflua Stokes suppresses invasion and migration of pancreatic cancer cells through downregulation of the JAK/STAT and Src/FAK signaling pathways

Abstract: Pancreatic cancer is a leading cause of mortality and morbidity worldwide. Due to drug resistance, and the high toxicity and adverse side effects of existing chemotherapeutic drugs, the current treatment of highly aggressive pancreatic cancer is considered inadequate. Allergen‑removed Rhus verniciflua Stokes (aRVS) has a strong antiproliferative effect in various cancer cells, and due to its low toxicity, it has emerged as an attractive candidate for cancer treatment. However, the potential use of aRVS as a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Therefore, prevention of angiogenesis is a valuable treatment for cancer, such as pancreatic cancer . Numerous studies have shown that specific molecules can affect the tumorigenesis, progression, incursion as well as migration of pancreatic cancer by participating in the regulation of JAK/STAT pathway . MAPKKK cascade is the key molecule in the MAPK pathway, and MAPK pathway can be incorporated to control cell propagation, invasion, migration, apoptosis, tumorigenesis, and progression of pancreatic tumor, as well as chemotherapy response and clinical outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, prevention of angiogenesis is a valuable treatment for cancer, such as pancreatic cancer . Numerous studies have shown that specific molecules can affect the tumorigenesis, progression, incursion as well as migration of pancreatic cancer by participating in the regulation of JAK/STAT pathway . MAPKKK cascade is the key molecule in the MAPK pathway, and MAPK pathway can be incorporated to control cell propagation, invasion, migration, apoptosis, tumorigenesis, and progression of pancreatic tumor, as well as chemotherapy response and clinical outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Numerous studies have shown that specific molecules can affect the tumorigenesis, progression, incursion as well as migration of pancreatic cancer by participating in the regulation of JAK/ STAT pathway. [41][42][43][44] MAPKKK cascade is the key molecule in the MAPK pathway, and MAPK pathway can be incorporated to control cell propagation, invasion, migration, apoptosis, tumorigenesis, and progression of pancreatic tumor, as well as chemotherapy response and clinical outcomes. [45][46][47][48][49][50][51] For the two drugs that were identified in our current study, no previous studies have identified their functions on cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many preclinical studies have been carried out on the anticancer effects of RVS [15,16,17,18,19,20,21], including, in two cases, clinical reports of treatment for metastatic renal cell carcinoma [22]. To our knowledge, there has been no report of an immuno-oncological study on RVS.…”
Section: Discussionmentioning
confidence: 99%
“…Several fractions and allergen-removed extracts from RVS have proven pharmacological effects, such as antioxidant [16,17], antimicrobial [18,19] or antiinflammatory effects [20,21]. In addition, anticancer activities of RVS in allergen-removed extracts have been reported in both experimental [22][23][24] and clinical studies [25]. We also reported the antiemetic and myelo-protective effects of allergen-removed RVS extracts using a cisplatin-injected animal model [26].…”
Section: Introductionmentioning
confidence: 87%